Corporate tax avoidance during Covid-19 pandemic : A study on public listed in Malaysia - Chik Mun, Keen (2023)
The main purpose of this study is to examine the impact of Company Size, Return on Assets (ROA), Capital Intensity (CAPR), Debt to Asset Ratio (DAR), Female Directors, and Company Age on Tax Avoidance in Bursa Malaysia's Public Listed Companies. Quantitative approach was adopted in this research. The sample selected based on top 30 and bottom 30 by market capitalization on the Main Board of Bursa Malaysia as at December 31, 2022. Based the results of study, it concluded Company size, Return On assets and Capital Intensity have significant impact on tax avoidance at 99%. It revealed Female Director has significant impact on tax avoidance at 95%. Whereas, Debt to Asset Ratio and Company Age do not have significant influence on tax avoidance.